Decade‐Long Nationwide Trends and Disparities in Use of Comfort Care Interventions for Patients With Ischemic Stroke - Chu, Kristie M.; Jones, Erica M.; Meeks, Jennifer R.; Pan, Alan P.; Agarwal, Kathryn L.; Taffet, George E.; Vahidy, Farhaan S. (Journal of the American Heart Association, 2021)
Background Stroke remains one of the leading causes of disability and death in the United States. We characterized 10-year nationwide trends in use of comfort care interventions (CCIs) among patients with ischemic stroke, particularly pertaining to acute thrombolytic therapy with intravenous tissue-type plasminogen activator and endovascular thrombectomy, and describe in-hospital outcomes and costs. Methods and Results We analyzed the National Inpatient Sample from 2006 to 2015 and identified adult patients with ischemic stroke with or without thrombolytic therapy and CCIs using validated ( codes. We report adjusted odds ratios (ORs) and 95% CI of CCI usage across five 2-year periods. Of 4 249 201 ischemic stroke encounters, 3.8% had CCI use. CCI use increased over time (adjusted OR, 4.80; 95% CI, 4.15-5.55) regardless of acute treatment type. Advanced age, female sex, White race, non-Medicare insurance, higher income, disease severity, comorbidity burden, and discharge from non-northeastern teaching hospitals were independently associated with receiving CCIs. In the fully adjusted model, thrombolytic therapy and endovascular thrombectomy, respectively, conferred a 6% and 10% greater likelihood of receiving CCIs. Among CCI users, there was a significant decline in in-hospital mortality compared with all other dispositions over time (adjusted OR, 0.46; 95% CI, 0.38-0.56). Despite longer length of stay, CCI hospitalizations incurred 16% lower adjusted costs. Conclusions CCI use among patients with ischemic stroke has increased regardless of acute treatment type. Nonetheless, considerable disparities persist. Closing the disparities gap and optimizing access, outcomes, and costs for CCIs among patients with stroke are important avenues for further research.